(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Background Pediatric leukemia is a severe medical condition and has a significant share in children’s cancers. The most frequent kind of cancer is Acute Lymphoblastic Leukemia (ALL), which has a high likelihood of a multi-directional combination of symptoms, issues with treatment, and conflicting outcomes. Identifying demographic and clinical variables influencing the outcome of treatment and survival is very important to improve pediatric oncology treatment. Aim The objective of the study was to assess the prognosis of children with leukemia diagnosis according to demographic characteristics, clinical p, treatment modalities, and long-term survival rate following a 12-month follow-up. Methods We conducted a cross-sectional study of 91 patients with pediatric leukemia. Data regarding the demographics, symptoms, and clinical characteristics, and treatment outcomes at one-year follow-up were collected from hospitals in Baghdad, Iraq, during January 2024 - January 2025. Statistical analysis were carried out to contrast demographic variables and survival results using SPSS version 22.0. Summary Results 51.6% of the cohort patients were male, with a large proportion (57.1%) having ALL. Presentation with fever (65.9%) and tiredness (54.9%) was frequent. Chemotherapy was given in most (82.4%), with treatment success overall at 76.9%. Survival at 12-month follow-up was 87.9%, with complete remission in 65.9% of the patients. Treatment side effects were seen in 22.0% of the patients, primarily as infections and neutropenia. Univariate analysis indicated that both leukemia type and age significantly influenced survival. Conclusion The results of the study point towards the significance of demographic as opposed to clinical factors in influencing treatment outcomes in patients with childhood leukemia. The very high survival rates reflect the efficacy of the current treatment regimens but highlight the need for customized approaches to managing complications and quality of life in children with leukemia..